2015
DOI: 10.1186/s40064-015-1252-8
|View full text |Cite
|
Sign up to set email alerts
|

Early mortality and functional outcome after acute stroke in Uganda: prospective study with 30 day follow-up

Abstract: Identification of early outcomes post stroke and their predictors is important in stroke management strategies. We prospectively analysed 30-day outcomes (mortality and functional ability) after stroke and their predictors among patients admitted within 7 days post event to a national referral hospital in Uganda. This was a prospective study of acute stroke patients consecutively enrolled between February and July 2014. Social demographics, clinical, laboratory, imaging characteristics, outcomes (all through 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
76
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(93 citation statements)
references
References 48 publications
15
76
2
Order By: Relevance
“…The research that does exist-largely from clinical studies outside of the United States and often dated-suggests that persons who are not married are more likely to die following a stroke than those who are married. [11][12][13][14] Although the evidence is limited, these findings are consistent with a large body of literature showing that individuals who are not married have fewer economic resources, less social support, more unhealthy behaviors, and ultimately worse health outcomes than their married counterparts. [15][16][17][18][19] To our knowledge, however, no existing studies have examined the association between marital status and the prospects of survival after stroke in the US population.…”
supporting
confidence: 73%
See 3 more Smart Citations
“…The research that does exist-largely from clinical studies outside of the United States and often dated-suggests that persons who are not married are more likely to die following a stroke than those who are married. [11][12][13][14] Although the evidence is limited, these findings are consistent with a large body of literature showing that individuals who are not married have fewer economic resources, less social support, more unhealthy behaviors, and ultimately worse health outcomes than their married counterparts. [15][16][17][18][19] To our knowledge, however, no existing studies have examined the association between marital status and the prospects of survival after stroke in the US population.…”
supporting
confidence: 73%
“…Whether and to what extent marital life is associated with one's prognosis after a stroke is not well documented. The research that does exist—largely from clinical studies outside of the United States and often dated—suggests that persons who are not married are more likely to die following a stroke than those who are married . Although the evidence is limited, these findings are consistent with a large body of literature showing that individuals who are not married have fewer economic resources, less social support, more unhealthy behaviors, and ultimately worse health outcomes than their married counterparts .…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…Consistently, our results showed that the NIHSS score in HCI patients with good clinical outcome was obviously higher than those with poor clinical outcome. Additionally, prior stroke and severe stroke at admission were prognostic factors for poor functional outcome [31,32]. In addition, the ADC results obtained from the core and the penumbra of the infarction area are believed to be beneficial in the estimation of the infarction prognosis and in the planning of a treatment protocol in ischemic stroke patients [33].…”
Section: Discussionmentioning
confidence: 99%